Koefisien Variabilitas Genetik dan Nilai Duga Heritabilitas Karakter Pertumbuhan Ikan Nila GIFT di Sukamandi - Didik Ariyanto (Universitas Gadjah Mada, 2006)
This study conducted to identify the genetic variability and heritability of nile tilapia strain GIFT (Genetic Improvement of Farmed Tilapia) cultured in Sukamandi, West Java. Analysis of morphology was measured with the conventional morphometric including total length, standard length, head length, maximum body depth, maximum body thickness and maximum body outliner. Genetic variability and broad sense heritability estimated with genotype and phenotype variance. The result showed that coefficient of genetic variability of total length, standard length, head length, maximum body depth, maximum body thickness and maximum body outliner were in low to moderate categories (0.48-3.78) and broad sense heritability estimation for this characters were in high categories (0.70-0.76).